(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The world’s national human capital as a whole is 64 % of the total national wealth. Human capital - an integral part of the country national wealth, which provides economic growth. Countries, whose policies are aimed at developing human potential, are the most successful. The article studies the state of Ukraine’s human capital. In the rating of the World Economic Forum on the educated human capital availability, Ukraine takes 34 place from 140 countries of the world The characteristics problems of human capital in the country are given. The real «points of pain», reflecting the current changes in human capital, is the outflow of qualified professionals to abroad, the birth rate decrease, mortality increase, an unhealthy lifestyle and a lack of mutual trust in society. Among other weighty negative trends, it is worth noting also the worsening of the conditions for the small business development, the career guidance lack for young people, environmental pollution, stress, and the civil liberties restriction.